Adhesive Capsulitis Mimicking Metastasis on 18F-FDG-PET/CT. (February 2015) - Salem, Usama; Zhang, Liping; Jorgensen, Jeffrey L.; Kumar, Rajendra; Amini, Behrang
<x xml:space="preserve">Abstract</x> Abstract A 70-year-old woman with squamous cell carcinoma of the lung and chronic lymphocytic leukemia/small lymphocytic lymphoma underwent PET/CT for initial staging. There was avid focal asymmetrical uptake at the left shoulder, concerning for metastasis. Magnetic resonance imaging performed for further evaluation showed an enhancing soft tissue process at the rotator interval. Clinical notes indicated a 6-month history of progressive left shoulder pain and limited range of motion. The magnetic resonance imaging appearance and patient's symptoms were characteristic of adhesive capsulitis. We describe a new location of benign FDG avidity at the rotator interval due to adhesive capsulitis that can mimic neoplasm.